Intervensi Edukatif Dalam Meningkatkan Partisipasi Skrining Kanker Serviks Pada Perempuan : A Systematic Review - Kodariyah Kodariyah; Tri Budiati; Wiwit Kurniawati (Journal of Pharmaceutical and Sciences, 2026)
Background: One of the most effective strategies for preventing cervical cancer is screening. In developing countries, the implementation and utilization of cervical cancer screening programs remain low. Educational interventions represent one strategy to increase participation in cervical cancer screening. Objective: This review aimed to identify educational interventions used to increase participation in cervical cancer screening. Methods: The inclusion criteria comprised studies that employed educational interventions to increase participation in cervical cancer screening. Literature searches were conducted in three databases—PubMed, Scopus, and ProQuest—and one search engine, ScienceDirect, for publications from 2020 to 2025. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Methodological quality was assessed using the JBI Critical Appraisal Checklist for Randomized Controlled Trials (RCTs). Results: A total of 10 studies involving 3,882 women who participated in educational interventions for cervical cancer screening were included. All included studies reported that educational interventions—delivered through face-to-face or digital approaches, and based on behavioral theories, community-based education, and couple-based education—were associated with improvements in knowledge, attitudes, risk perception, self-efficacy, and participation in cervical cancer screening. Based on the JBI Critical Appraisal Checklist for RCTs, most studies demonstrated moderate to high methodological quality. Conclusion: Couple-based education and counselling demonstrate high potential for implementation in Indonesia. This educational approach may help address cultural barriers and limited family support, which are known to hinder participation in cervical cancer screening.